The Cost of Preventing Readmissions: Why Surgeons Should Lead the Effort. Issue 10 (October 2014) - Postel, Mackenzie; Frank, Paul N.; Barry, Tod; Satou, Nancy; Shemin, Richard; Benharash, Peyman
In accordance with the Affordable Care Act, Medicare has instituted financial penalties for hospitals with 30-day readmission rates that exceed a predetermined value. Currently, this value only considers "excess" readmissions for myocardial infarction, heart failure, and pneumonia with a maximum fine being one per cent of total Medicare reimbursements. In 2015, this penalty will increase to three per cent and encompass more surgical diagnoses. We retrospectively reviewed a database of adult patients undergoing cardiac surgery treated at our institution in 2012 to establish whether patients with readmissions within 30 days of the index operation could have been managed more cost-effectively without readmission. A calculation of cost efficiency was performed to compare the net hospital profit for two scenarios: admitting patients versus hypothetical preventative measures. Of the 576 patients during the study period, a total of 68 (11.8%) patients with unplanned 30-day readmissions were identified. Outpatient management was determined to have been feasible for 18 (26.5%) patients. Whereas the calculated net profit for readmission was $144, 000, inclusion of Medicare's penalty resulted in a loss of $11, 950. A readmission reduction program with an annual cost exceeding $11, 950 would lead to financial loss. The financial implications of Medicare's readmission penalty alone necessitate the development of cost-effective strategies to reduce rehospitalization.